The association between diabetes status and survival following an out-of-hospital cardiac arrest: A retrospective cohort study. (April 2017) - Parry, Monica; Danielson, Kyle; Brennenstuhl, Sarah; Drennan, Ian R.; Morrison, Laurie J.
Abstract: Background: Sudden cardiac arrest (SCA), confirmed absence of cardiac mechanical activity, is the leading cause of heart-related death in the US. Almost 85% of SCA occur out-of-hospital (OHCA), with very poor rates of return of spontaneous circulation (ROSC) and survival to hospital discharge. We sought to determine if diabetes status was associated with survival or ROSC following an OHCA. Methods: We completed a retrospective cohort study using data from the Toronto Regional RescuNet Epistry dataset, based upon data definitions defined by the Resuscitation Outcomes Consortium (ROC) Epistry-Cardiac Arrest and the Strategies for Post Arrest Resuscitation Care (SPARC) network datasets. Adults ≥18 years of age who experienced an OHCA, had data on diabetes status, and were treated by Emergency Medical Services (EMS) between 2012–2014 were included in the analysis (n = 10, 097). We used bivariate analyses to examine relationships between diabetes status, Utstein elements and outcomes, and logistic regression to determine predictors of survival. Results: Diabetes prevalence was 27.8% (95% CI: 27.0–28.7). A larger proportion of those with diabetes had a non-shockable initial rhythm (28.8% vs. 25.1%; p < 0.01) and did not survive to hospital discharge (92.1% vs. 89.2%, p < 0.001). Diabetes status is associated with a decrease in survival, independent from a number of Utstein elements (adjusted OR = 0.76; 95% CI: 0.64–0.91, p = 0.003). Conclusions: This is the first Canadian study to examine the association between diabetes status and OHCA outcomes. Our findings suggest that diabetes status prior to arrest is associated with decreased survival. The growing prevalence of diabetes globally suggests a future burden related to OHCAs.